2002
DOI: 10.2466/pms.2002.95.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Inexperienced Sport Climbers Might Perceive and Utilize New Opportunities for Action by Merely Observing a Model

Abstract: The purpose of this study was to evaluate whether observing an expert climber would enable inexperienced climbers to perceive and accomplish new possibilities for action and whether this would facilitate their climbing performance. The focus was on what information is obtained during observation of a motor action. Three groups of inexperienced male participants (N = 24) observed either a video model of an expert method of climbing, a video model of a novice method of climbing, or the climbing wall on video wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 7 publications
3
35
0
Order By: Relevance
“…The higher the entropy value, the higher the irregularity of the climbing trajectory, whereas the lower the entropy value, the more regular is the route trajectory. GIE has a number of advantages over other reported spatial variables (such as the average movement distance [7]) in that it is readily interpreted with respect to climbing activity, accounts for climb height and, shown to be effective for detecting skill [2], practice [2], route [8] and technique effects in climbing tasks [5,9]. Furthermore, data collection to perform an entropy calculation is relatively straight forward, involving use of a single camera [10].…”
Section: Responsementioning
confidence: 99%
“…The higher the entropy value, the higher the irregularity of the climbing trajectory, whereas the lower the entropy value, the more regular is the route trajectory. GIE has a number of advantages over other reported spatial variables (such as the average movement distance [7]) in that it is readily interpreted with respect to climbing activity, accounts for climb height and, shown to be effective for detecting skill [2], practice [2], route [8] and technique effects in climbing tasks [5,9]. Furthermore, data collection to perform an entropy calculation is relatively straight forward, involving use of a single camera [10].…”
Section: Responsementioning
confidence: 99%
“…Similarly, Seifert et al [26] showed that specific characteristics of acquired coordination patterns support performance fluency (see also Boschker and Bakker [52]). Seifert et al [26] tested transfer of experienced rock climbers and inexperienced rock climbers when climbing in an unfamiliar ice-climbing environment.…”
Section: Skill a E P Edi Ted A Oss A A Ge Of Oo DI Atio A Ia Les mentioning
confidence: 99%
“…Broadly, practice effects indicate that exploratory behaviours reduce with practice [39,96] whilst indicators of improved efficiency increase [24,39,44,52,80,95]. Boschker and…”
Section: E Plo Atio a D P A Ti E I P O Es Fluementioning
confidence: 99%
See 2 more Smart Citations